Turning Bone Morphogenetic Protein 2 (BMP2) On and Off in Mesenchymal Cells() - Rogers, Melissa B. (J Cell Biochem, 2015)
The concentration, location, and timing of bone morphogenetic protein 2 (BMP2, HGNC:1069, GeneID: 650) gene expression must be precisely regulated. Abnormal BMP2 levels cause congenital anomalies and diseases involving the mesenchymal cells that differentiate into muscle, fat, cartilage, and bone. The molecules and conditions that influence BMP2 synthesis are diverse. Understandably, complex mechanisms control Bmp2 gene expression. This review includes a compilation of agents and conditions that can induce Bmp2. The currently known trans-regulatory factors and cis-regulatory elements that modulate Bmp2 expression are summarized and discussed. This article is protected by copyright. All rights reserved